2016
DOI: 10.1093/jxb/erw285
|View full text |Cite
|
Sign up to set email alerts
|

Responses to combined abiotic and biotic stress in tomato are governed by stress intensity and resistance mechanism

Abstract: HighlightSalt stress severity differentially affected partial powdery mildew resistance. Stress combination uniquely resulted in accelerated senescence. mlo-based and R-gene-mediated resistance maintained robustness across salt treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 80 publications
8
78
0
Order By: Relevance
“…As shown previously (Kissoudis et al, 2016), NIL-ol-2 exhibited increased callose deposits compared to NIL-Ol-1 and MM upon PM infection, and additional salt stress decreased callose deposits in all genotypes ( Figure 5 ). Under only PM infection, the epi mutation resulted in a near complete absence of callose deposits in the crosses with Ol-1 and ol-2 .…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…As shown previously (Kissoudis et al, 2016), NIL-ol-2 exhibited increased callose deposits compared to NIL-Ol-1 and MM upon PM infection, and additional salt stress decreased callose deposits in all genotypes ( Figure 5 ). Under only PM infection, the epi mutation resulted in a near complete absence of callose deposits in the crosses with Ol-1 and ol-2 .…”
Section: Resultssupporting
confidence: 87%
“…These lines were studied in more detail under control conditions, salt stress (50 mM), PM inoculation, and combined salt stress and PM inoculation, allowing an assessment of growth performance costs under the different stress conditions. These Ol -gene and mutant combinations are particularly interesting as ABA is the major hormone orchestrating abiotic stress responses in plants (Yoshida et al, 2014), while ET signaling was shown to be crucial for plant susceptibility and senescence responses under combined stress (Kissoudis et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations